The Ends of Modernization : Nicaragua and the United States in the Cold War Era - Lee, David Johnson, 1978- (Book collections on Project MUSE., 2021)
"This book studies the relations between Nicaragua and the United States during and after the Cold War to understand the transformation of the ideals of modernization, national autonomy, and planned development as they gave way to human rights protection, neoliberalism, and sustainability as global ideals"--